Efficacy of Rifaximin in Diarrhoea Predominant Irritable Bowel Syndrome: A Placebo Controlled Clinical Trial (Medicine Today, 2023)
Introduction: Irritable bowel syndrome is a common chronic functional gastrointestinal disorder characterized by abdominal pain associated with altered bowel habit of either diarrhoea, constipation or both. Its pathogenesis is multifactorial and incompletely understood.The role of gut microbiota in the pathophysiology of IBS is supported by various evidences.These are differences in mucosal and faecal microbiota between patients with IBS and healthy individuals,development of post-infectious IBS and the efficacy of some probiotics and nonsystemic antibiotics such as Rifaximin. Previous study showed resetting microbial diversity via Rifaximin use may lead to a decrease in bacterial fermentation and a reduction in the clinical symptoms of IBS. This study is designed to assess efficacy of Rifaximin in diarrhoea predominant irritable bowel syndrome.Objective: This study was conducted to assess the effectiveness of Rifaximin in diarrhoea predominant irritable bowel syndrome patient.Materials and Methods: This quasi experimental study was conducted on patients aged 18-55 years with IBS-D in department of Gastroenterology, BSMMU during the period of September, 2020 to August, 2021.Results: There was significant improvement on abdominal pain(p